A Luxurious Royal Estate from the First Temple Period in Armon ha-Natziv, Jerusalem. (2nd January 2022) - Billig, Yaʿakov; Freud, Liora; Bocher, Efrat
Abstract : In a recent excavation at Armon ha-Natziv, overlooking ancient Jerusalem, remains were uncovered of a royal estate from the second half of the 7th century BCE. Although the site had been dismantled and it appears that only a small portion of it has been exposed to date, there are several indications of its former grandeur. The excavations exposed three complete medium-sized decorated volute capitals, beautifully carved and excellently preserved. Dozens of fragments of adorned architectural elements were exposed nearby; they can be restored to compose a window frame with an ornamented balustrade of miniature pillars capped with decorated volute capitals. Together with fragments of ashlars bearing traces of paint, they all appear to originate from a luxurious palace or villa. A rock-cut latrine with a seat—a marker of wealth in antiquity—was uncovered above a septic pit; microscopic examination detected parasite eggs from the digestive system, along with pollen from a variety of plants that grew on the grounds. This article examines the status of this unique site among the other Judahite sites in the region, in which contemporaneous monumental architectural finds indicate an administrative or government-oriented status.